BEHAVIOR OF INDIVIDUAL TAXPAYERS AND CORPORATE TAXPAYERS IN THE IMPLEMENTATION OF SELF ASSESSMENT SYSTEM - Abdul Muis, 08.05.52.0190; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2012)
The purpose of this study is to investigate and analyze the application of functions to calculate, pay, reporting, counseling, supervision, and services in the self assessment system at KPP Pratama Semarang Barat.This study population penghasilah tax only on the individual taxpayer who has a free employment agency and taxpayers residing in KPP Pratama Semarang Barat. Sampling technique using purposive sampling. Source of data is primary data obtained by distributing questionnaires and interviews directly from the 2nd of January to February 2, 2012 obtained the data as much as 53 individual taxpayer and the taxpayer Agency 50 persons. Mechanical analysis of qualitative data using descriptive statistics with percentages.The results showed that the self assessment system has not been implemented properly. Proved most taxpayers do not calculate their own taxes even if the taxpayer has to pay taxes on time. Taxpayers tax report is not due to consciousness, but because of fear of fines. Information about the extension has not been implemented properly. Tax officials have not implemented the system with good judgment, but its also a supervisory function carried too far. So also with the officials have not implemented the service tax to the max.Keywords: taxpayers, tax authorities, self assessment system